Peritoneal GATA6+ macrophage drives hepatic immunopathogenesis and maintains the Treg cell niche in the liver. Issue 1 (30th June 2022) - Chang, Hao; Ni, Yangyue; Shen, Chunxiang; Li, Chen; He, Kaiyue; Zhu, Xinyi; Chen, Lin; Chen, Lu; Qiu, Jingfan; Ji, Yong; Hou, Min; Ji, Minjun; et al.
Abstract: The source of macrophages that contribute to human liver disease remains poorly understood. The purpose of this study is to investigate the functional mechanism of peritoneal macrophages in the development of hepatic immunopathology. By performing the natural infection with the blood fluke Schistosoma japonicum ( S. japonicum ) and the chemically carbon tetrachloride (CCl4 )‐induced liver injured mouse model, we identified the peritoneal cavity as an essential source of hepatic macrophages. Here, we show that a large number of F4/80 + macrophages was accumulated in the peritoneal cavity during liver injury. An unknown source population of macrophages, which highly expressed GATA6 that is specific to peritoneal macrophages, was found to exist in the injured livers. Peritoneal macrophage deletion by injection with clodronate‐containing liposomes led to an attenuated hepatic pathology and the inflammatory microenvironment, while adoptive transfer of macrophages into the abdominal cavity, by contrast, results in restoring liver pathology. Importantly, there are set genes of monocyte chemoattractant protein (MCP)‐1, ‐2, and ‐3 that are highly related to recruit GATA6 + macrophages during S. japonicum infection, while administration of bindarit, a selective inhibitor of MCPs synthesis, dramatically decreased the hepatic expression of GATA6 + macrophages and thus attenuated hepatic pathology. Furthermore, in vivo study showed that peritoneal macrophages promote hepatic immunopathology is dependent on the accumulation of regulatory T cells (Tregs) in the liver. Altogether, these data provide the first clear evidence that GATA6 + peritoneal macrophages play critical roles in both the formation of hepatic immunopathology and the accumulation of Tregs cells. Abstract : The infiltration of peritoneal GATA6 + macrophage is an important mechanism for cellular accumulation in the liver during pathogen‐ or chemical‐induced hepatic immunopathology. The local hepatic MCPs mediate delivery of peritoneal macrophages through CCR2 while the applications of MCPs antagonist bindarit could improve hepatic immunopathology. In addition, peritoneal macrophages play a major role in the induction of hepatic regulatory T cells that involved in the suppression of hepatic immunopathology.